Teachers’ and School Psychologists’ Roles in Post-Diagnostic Educational Planning for Learners with Intellectual Disability in Calabar Metropolis, Nigeria - Edu Edu, Grace Onya; Aderibigbe, Samson Akinwonmi; Uwe, Uduak Edet; Etta, Idaka Etta; Otu, Ebeten Bassey; Undie, Akomaye Agwu; Effiom, Veronica Nakanda; Bisong, Catherine Ejor; Anoh, Janet Menku; James, Daniel Daniel; Eko, Promise Ogban; Ahmad, Abdullahi Abdallah; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
This study examined the roles of teachers and school psychologists in post-diagnostic educational planning for learners with intellectual disability in Calabar Metropolis, Cross River State, Nigeria. It aimed to investigate how diagnostic information is translated into educational plans, how professional roles are enacted and coordinated, and the extent to which these processes influence the quality of individualized educational support. A descriptive survey design was adopted, involving 202 teachers and 68 school psychologists selected through a multi-stage sampling technique. Data were collected using a validated and reliable Questionnaire on Post-Diagnostic Planning (Cronbach’s alpha = 0.81). Analyses included independent-samples t-tests, Pearson correlations, one-way ANOVA, Tukey HSD post hoc tests, and multiple regression, all conducted at the 0.05 significance level. Findings revealed no significant difference between teachers’ and psychologists’ roles in planning (t = -1.02, p = 0.309), but collaboration between teachers and psychologists positively correlated with planning effectiveness (r = 0.61, p < 0.001). Professional qualification significantly influenced teachers’ effectiveness (F = 6.84, p = 0.002), while years of experience significantly enhanced psychologists’ effectiveness (F = 5.91, p = 0.004). Moreover, institutional support significantly predicted planning quality (β = 0.48, t = 8.21, p < 0.001). The study concludes that effective post-diagnostic educational planning depends on human factors (experience and qualifications), organizational support, and interprofessional collaboration. These findings highlight the need for capacity-building programs, structured collaborative practices, and supportive institutional policies to enhance educational outcomes for learners with intellectual disabilities.